Do Employees Cheer for Private Equity? The Heterogeneous Effects of Buyouts on Job Quality - Gornall, Will; Gredil, Oleg R.; Howell, Sabrina T.; Liu, Xing; Sockin, Jason (Management Science, 2025)
We show that private equity leveraged buyouts reduce perceived job quality despite not impacting average base pay. This appears to reflect employees bearing more risk. Both job quality and employee incentive pay are more related to firm performance at private equity-owned companies than at public control firms with 1% higher deal rate of return associated with 0.7% more employee incentive pay. Deals with high leverage and employees with worse outside options fuel the declines in job satisfaction after a buyout. Our results highlight how job quality is tied to job security and how ownership affects employees through mechanisms beyond base pay. This paper was accepted by David Sraer, finance. Funding: W. Gornall thanks the Social Sciences and Humanities Research Council Insight Development [Grant 430-2019-00306] for its support and gratefully acknowledges that this research was undertaken, in part, thanks to funding from the Canada Excellence Research Chairs program awarded to Dr. Erik Snowberg in data-intensive methods in economics. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2022.00951 .